THE IMPACT OF FINANCIAL DEVELOPMENT AND FINANCIAL INCLUSION ON INCOME INEQUALITY: EVIDENCE FROM OECD COUNTRIES (The South East European Journal of Economics and Business, 2026)
This study examines the relationships between financial sector development, financial inclusion, and income inequality in OECD countries by utilizing panel data from 38 countries for the period 2010-2022. The impact of financial sector development and financial inclusion on Gini coefficient is examined, while applying fixed effects, random effects and GMM modeling. The results suggest that financial inclusion is associated with lower income inequality, while the effect of financial development, proxied by private sector credit, is positive but not statistically robust. We find that financial development, measured by private‑sector credit, is associated with higher income inequality — a pattern consistent with credit concentration in favor of higher‑income groups — whereas financial inclusion is associated with lower inequality, through channels of broadened access to savings, credit, and risk‑management. This study adds value to the existing literature by providing new empirical evidence on the dynamic interplay between financial and real sectors.